2014
DOI: 10.1155/2014/713531
|View full text |Cite
|
Sign up to set email alerts
|

Development of UHPC Mixtures Utilizing Natural and Industrial Waste Materials as Partial Replacements of Silica Fume and Sand

Abstract: In the exploratory study presented in this paper, an attempt was made to develop different mixtures of ultrahigh performance concrete (UHPC) using various locally available natural and industrial waste materials as partial replacements of silica fume and sand. Materials such as natural pozzolana (NP), fly ash (FA), limestone powder (LSP), cement kiln dust (CKD), and pulverized steel slag (PSS), all of which are abundantly available in Saudi Arabia at little or no cost, were employed in the development of the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 9 publications
2
29
0
1
Order By: Relevance
“…When CS content increases up to 16% of the binder, the compressive strength of UHPC increases by 3.1% at 90 days. Ahmadm et al studied the effect of using industrial waste materials like PSS to replace parts of SF [ 49 ]. When replacing 20% of SF, the compressive strength of UHPC can still reach 161 MPa at 28 days, which is the same as that of the reference specimen with SF only and flow diameter slightly decreased, but it was still within the acceptable range.…”
Section: Effect Of Scms On Materials Properties Of Uhpcmentioning
confidence: 99%
See 2 more Smart Citations
“…When CS content increases up to 16% of the binder, the compressive strength of UHPC increases by 3.1% at 90 days. Ahmadm et al studied the effect of using industrial waste materials like PSS to replace parts of SF [ 49 ]. When replacing 20% of SF, the compressive strength of UHPC can still reach 161 MPa at 28 days, which is the same as that of the reference specimen with SF only and flow diameter slightly decreased, but it was still within the acceptable range.…”
Section: Effect Of Scms On Materials Properties Of Uhpcmentioning
confidence: 99%
“…As a pozzolanic material, it is known that FA increases the late age strength of conventional cementitious material. The usage of FA can reduce CO 2 emissions [ 55 , 66 ] and decrease the production cost and energy of concrete [ 41 , 49 , 53 , 55 ]. In recent years, many researchers have focused on developing new UHPC mixtures with locally available FA because substituting cement and/or SF with FA can reduce environmental impacts.…”
Section: Effect Of Scms On Materials Properties Of Uhpcmentioning
confidence: 99%
See 1 more Smart Citation
“…Recycled glass powder, fluid catalytic cracking catalyst residue and limestone powder are some of the supplementary cementitious materials (SCM) that can be used as a partial substitution of Portland cement in UHPC [12,[19][20][21]. There are several UHPC mixture proportions from the literature using glass powder or limestone powder as a component of UHPC's binder.…”
Section: Introductionmentioning
confidence: 99%
“…Using various locally available materials in Saudi Arabia, such as limestone powder. Ahmad et al [20] showed the possibility of partial substitution of cement and silica fume without affecting the rheological and mechanical properties of UHPC. Even nano-CaCO3 was used as a component of the binder [23].…”
Section: Introductionmentioning
confidence: 99%